Spirituality and mental health status among Northern Plain tribes. Issue 3 (16th March 2018) - Bear, Ursula Running; Garroutte, Eva Marie; Beals, Janette; Kaufman, Carol E.; Manson, Spero M.
ABSTRACT: Spirituality measures often show positive associations with preferred mental health outcomes in the general population; however, research among American Indians (AIs) is limited. We examined the relationships of mental health status and two measures of spirituality – the Midlife Development Inventory (MIDI) and a tribal cultural spirituality measure – in Northern Plains AIs, aged 15–54 ( n  = 1636). While the MIDI was unassociated with mental health status, the tribal cultural spirituality measure showed a significant relationship with better mental health status. Mental health conditions disproportionately affect AIs. Understanding protective factors such as cultural spirituality that can mitigate mental health disorders is critical to reducing these health disparities.